2D RESISTIVITY TIME LAPSE ANALYSIS FOR POTENTIAL ZONING SLIDE WET MUD IN PANEL 7 DEEP ORE ZONE (DOZ) - Felisitas K. Ulian; Jeffri Parrangan (Musamus Journal of Science Education, 2019)
Abstract High rainfall may disrupt mining operations due to possibility of wet mud slides, occurences. One of the area wet mud slide in the mining area of "DOZ" Panel 7 West PT Freeport Indonesia, Mimika District, Papua Province. Study was needed to image the subsurface where have high probability of wet mud slide might happen. Resistivity method was used using Wenner Alpha configuration with a total length of 270 m. The measurements were performea six times at different dates. Measured data use as the primary data to determine the high possibility areas of mud wet slides. And the primary data were compared with secondary data such as rainfall and geological data. Analysis the resistivity cross-sections show that the low resistivity zones are located in Panel 7 DP # 14E, 16E, 18E, 19E, 20E and 21E. Water enter the DOZ Mine (Deep Ore Zone) by infiltration and precipitation directly through the cave material, permeable zones along the contact zone of diorite/skarn/marble, and the spillover cut crackline or caveline of formation Lower Kais. The correlation between the quantitative data of the apparent resistivity with rainfall data has the highest value of 3.52 %. Keywords: Resistivity, wet muck, panel